2021
DOI: 10.1177/2473974x211067423
|View full text |Cite
|
Sign up to set email alerts
|

Utility of the Modified and High‐Sensitivity Modified Glasgow Prognostic Scores for Hypopharyngeal Squamous Cell Carcinoma

Abstract: Objective To determine whether the modified Glasgow prognostic score (mGPS) and high-sensitivity mGPS (HS-mGPS) could predict outcomes among patients with hypopharyngeal squamous cell carcinoma (HSCC). Study Design Retrospective cohort study. Setting Affiliated university hospital. Methods We reviewed the records of 115 patients with histologically confirmed HSCC between March 2007 and December 2019. Univariate and multivariable Cox proportional hazard analyses were performed for overall survival (OS) and dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…The sample sizes ranged from 70 to 1625 (median: 163). Among them, 13 studies [ 7 , 14 , 15 , 16 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ] (4651 cases) used multivariable analysis and 4 studies [ 30 , 31 , 32 , 33 ] (1177 cases) used univariable analysis in survival outcome measurement. This meta-analysis analyzed multiple cancer types, including gastrointestinal cancer (3 gastric cancers [ 16 , 30 , 31 ], 1 hepatocellular carcinoma [ 28 ], 1 esophageal cancer [ 14 ], 1 gallbladder cancer [ 32 ], and 1 colorectal cancer [ 29 ]), head and neck cancer (1 head and neck cancer [ 22 ], 1 oropharyngeal cancer [ 26 ], 1 hypopharyngeal cancer [ 27 ], and 1 oral cancer [ 7 ]), soft tissue sarcoma (3 soft tissue sarcoma [ 21 , 23 , 33 ] and 1 neuroblastoma [ 24 ]), non-small-cell lung cancer [ 15 ] (n = 1), and prostate cancer [ 25 ] (n = 1).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The sample sizes ranged from 70 to 1625 (median: 163). Among them, 13 studies [ 7 , 14 , 15 , 16 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ] (4651 cases) used multivariable analysis and 4 studies [ 30 , 31 , 32 , 33 ] (1177 cases) used univariable analysis in survival outcome measurement. This meta-analysis analyzed multiple cancer types, including gastrointestinal cancer (3 gastric cancers [ 16 , 30 , 31 ], 1 hepatocellular carcinoma [ 28 ], 1 esophageal cancer [ 14 ], 1 gallbladder cancer [ 32 ], and 1 colorectal cancer [ 29 ]), head and neck cancer (1 head and neck cancer [ 22 ], 1 oropharyngeal cancer [ 26 ], 1 hypopharyngeal cancer [ 27 ], and 1 oral cancer [ 7 ]), soft tissue sarcoma (3 soft tissue sarcoma [ 21 , 23 , 33 ] and 1 neuroblastoma [ 24 ]), non-small-cell lung cancer [ 15 ] (n = 1), and prostate cancer [ 25 ] (n = 1).…”
Section: Resultsmentioning
confidence: 99%
“…Among them, 13 studies [ 7 , 14 , 15 , 16 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ] (4651 cases) used multivariable analysis and 4 studies [ 30 , 31 , 32 , 33 ] (1177 cases) used univariable analysis in survival outcome measurement. This meta-analysis analyzed multiple cancer types, including gastrointestinal cancer (3 gastric cancers [ 16 , 30 , 31 ], 1 hepatocellular carcinoma [ 28 ], 1 esophageal cancer [ 14 ], 1 gallbladder cancer [ 32 ], and 1 colorectal cancer [ 29 ]), head and neck cancer (1 head and neck cancer [ 22 ], 1 oropharyngeal cancer [ 26 ], 1 hypopharyngeal cancer [ 27 ], and 1 oral cancer [ 7 ]), soft tissue sarcoma (3 soft tissue sarcoma [ 21 , 23 , 33 ] and 1 neuroblastoma [ 24 ]), non-small-cell lung cancer [ 15 ] (n = 1), and prostate cancer [ 25 ] (n = 1). A total of 12 studies reported cancer stage according to the TNM staging system, while 6 studies reported stage according to other staging systems, including the French Federation of Cancer Centers Sarcoma Group grading system, the Barcelona Clinic Liver Cancer staging system, the Japanese Gastric Cancer Treatment Guidelines, and the International Neuroblastoma Staging System.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations